(untitled) (Journal of Global Accounting, 2024)
The study evaluated the effect of intellectual capital efficiency on the corporate performance of quoted manufacturing companies in Nigeria. The population of the study consists of 20 companies quoted on the Nigeria stock exchange under the consumer goods sector as at 2019. A total of sixteen (16) companies with updated financial information for the relevant years were selected and analyzed. Data for the study were extracted from annual reports and accounts of selected companies for the period 2012-2018. The study applied the Value Added Intellectual Coefficient (VAIC) model. Three research hypotheses were formulated for the study. In testing the research hypotheses, the study adopted both descriptive statistics and multiple panel regression techniques for quoted sampled firms analyzed with the aid of E-Views version 9. The findings revealed that Intellectual capital (IC) has a positive significant effect on ROCE and ROA. There was no significance found for earnings per share. Based on the findings, it was concluded that intellectual capital has a significant and positive effect on the corporate performance of manufacturing firms in Nigeria. Consequent upon this, the study, it was recommended that adequate attention be given to firm’s human capital since human capital efficiency is considered as the most important asset of any organization.